Analisis Pengaruh Brand Ambassador, Online Customer Review, dan Digital Marketing Terhadap Keputusan Pembelian Hansui - JC Syamsia (MES Management Journal, 2025)
This study uses a quantitative, causal associative research approach to examine the impact of Brand Ambassador, Online Customer Review, and Digital Marketing on Hansui product purchases among Halmahera University students. Data were gathered via a questionnaire with 44 students who had previously purchased Hansui products as respondents. The data was analyzed using multiple linear regression, validity, reliability, F, and t tests. The findings indicated that all three independent variables simultaneously had a substantial influence on purchase decisions, with a coefficient of determination (R2) of 0.838. Purchase decisions were significantly influenced by digital marketing and online customer reviews, whereas brand ambassadors had no discernible influence. Business actors can use this study as a strategic guidance when developing targeted promotions, and it contributes to the body of literature on digital marketing.